Code-Switching in Bilingual Adolescents: A Psycholinguistic Analysis - Tiara Ayunda, Rizki; Widyana, Airen; Saharani, Dea; Lubis, Yani (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study explores code-switching behavior among bilingual adolescents through a psycholinguistic lens, focusing on the cognitive, social, and communicative motives behind their language alternation. As bilingualism becomes more common in multicultural environments, understanding how adolescents navigate between two languages provides valuable insight into their linguistic development and identity formation. Using a qualitative descriptive approach, the research analyzes natural conversations, interviews, and contextual factors that influence the choice of switching codes. The findings indicate that code-switching serves as a strategic tool to enhance clarity, express emotions, maintain social relationships, and negotiate cultural identity. Psycholinguistically, adolescents demonstrate high cognitive flexibility as they move between languages, revealing a strong command of linguistic structures and an ability to adapt language use based on listeners and situations. Additionally, emotional expression often becomes more nuanced when switching codes, especially in peer interactions. The study concludes that code-switching among bilingual adolescents is not a sign of linguistic deficiency, but rather a sophisticated and functional skill shaped by cognitive processes and social dynamics. Understanding these patterns contributes to broader knowledge on bilingual language development and provides implications for education, communication, and cultural studies.